2018
DOI: 10.1055/a-0782-0548
|View full text |Cite|
|
Sign up to set email alerts
|

Piper nigrum Oil – Determination of Selected Terpenes for Quality Evaluation

Abstract: The growing demand and commercial value of black pepper (Piper nigrum) has resulted in considerable interest in developing suitable and cost-effective methods for chemical characterization and quality evaluation purposes. In the current study, an extensive set of oil samples (n = 23) that were extracted by steam distillation from black pepper seeds was investigated to compare the chemical profiles of samples originating from nine major producing countries, as well as to identify potential chemical markers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…However, it is important to collect more pepper samples to establish the authenticity and quality of white and black pepper from different cultivar by Q-markers. 16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to collect more pepper samples to establish the authenticity and quality of white and black pepper from different cultivar by Q-markers. 16…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the quality of black pepper oil is regulated under the International Standard Organization (ISO) "ISO 3061:2008 Oil of black pepper (P. nigrum L.)", in which the content of some major chemical constituents from 4 countries, including India, Sri Lanka, Indonesia, and Madagascar, was limited. 16 For example, it suggested that the content of β-pinene of the black pepper EOs produced in India should be 5%-12%. The content of β-selinene was 3%-6% in the EOs of black pepper produced in Indonesia.…”
Section: The Chemical Compositions Of the Eos From The Pepper Samplesmentioning
confidence: 99%
“…Compound 2 is biogenetically derived from L-lysine, which is converted to piperidine, precursor of piperidone, and further catalysis by chloroperoxidase (CPO) in the last step of its biosynthesis yield 2. Moreover, compound 12 could be derived from L-phenylalanine by the typical of shikimic acid pathway through cinnamic acid (10), which is the precursor of ferulic acid (11). Precursors 10 and 11 were also isolated from the plant (Scheme 1).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…terpenoids [11], phenylpropanoids [12], phenolic acids [13] and lignans [14]. These constituents have been reported to possess antioxidant [10], anti-inflammatory [15], antitumor [16] and antiparasitic properties [13,14,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation